2005
DOI: 10.2166/wst.2005.0657
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating membrane gas diffusion into a membrane bioreactor for hydrogenotrophic denitrification of groundwater

Abstract: A hydrogenotrophic denitrification system, comprising a suspended growth membrane bioreactor (MBR) with membrane hydrogen gas diffusion, was developed to remove nitrate from groundwater. A hollow fiber gas permeable membrane module was designed for hydrogen delivery and a commercially available hollow fiber membrane module was used for solid/liquid separation. The MBR was operated at an SRT of 20 days and at room temperature. Four nitrate loading rates of 24, 48, 96 and 192 NO3(-)-N mg I(-1) d(-1) were applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 0 publications
0
23
0
3
Order By: Relevance
“…In addition, the growth rate of autotrophic denitrifying bacteria ensures low biomass build-up and limited operating problems. Thus, hydrogenotrophic bacteria have been successfully used for drinking water nitrate elimination to acceptable levels either in pure [4][5][6][7] or in mixed-cultures [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the growth rate of autotrophic denitrifying bacteria ensures low biomass build-up and limited operating problems. Thus, hydrogenotrophic bacteria have been successfully used for drinking water nitrate elimination to acceptable levels either in pure [4][5][6][7] or in mixed-cultures [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many different technologies for hydrogenotrophic denitrification have been developed in an effort to solve the problem of NO 3 − in drinking water or wastewater, e.g., membrane reactors [3][4][5][6][7], bio-electrochemical systems [8], fluidized-bed reactors [9,10] and fixed-bed reactors [11,12]. Packed-bed reactors, provide a support medium for biofilm growth (higher biomass concentration), thus allowing the possibility of maintaining bacteria at high hydraulic and nitrogen loadings.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, NO 3 -N was removed by hydrogenotrophic denitrification, as presented in Equation 4 [23]). From the results, it can be concluded that the NO 3 -N bioreactor can remove NO 3 -N from groundwater at a very high efficiency, and moreover, this system has advantages of being simple, easy to operate and requiring less H 2 comparing to the reactors used in previous studies [24,25] …”
Section: Performance Of No 3 -N Bioreactormentioning
confidence: 88%